Crossing oceans for healthcare - Lee, Elizabeth Ying Qi (Nanyang Technological University, 2020)
In the last decade, Malaysia’s medical tourism industry has more than doubled in size, recording more than 665,000 international healthcare tourists in 2018, up from just 325,000 in 2011. Healthcare traveller revenue has also increased from about RM300m in 2011 to more than RM900m in 2018. With the launch of the Malaysia Year of Healthcare Travel 2020 last November, the nation is further increasing efforts to establish itself as a global destination for healthcare travellers.